EFFECT OF EXERCISE SKIP FOR HEIGHT TO POWER LEG MUSCLE IN THE MEN’S VOLLEYBALL TEAM PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI PEKANBARU - Nurbaeti '; Saripin '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT : The issues raised in this study is " What is the effect of exercise skip for height To power leg muscle In the men’s volleyball team Panti Sosial Bina Remaja (PSBR) Rumbai Pekanbaru?". This research is experimental research that aims to find out the effect of exercise skip for height To power leg muscle In the men’s volleyball team Panti Sosial Bina Remaja (PSBR) Rumbai Pekanbaru. Population used was the entire men’s volleyball team Panti Sosial Bina Remaja (PSBR) Rumbai Pekanbaru as many as 12 people.This study uses total sampling technique the entire population sampled. Based on the determination of sample, the sampel of 12 people. As the independent variable (x) was training skip for height while the dependent variable (y) is the power leg muscle. Were obtained and collected through the initial test and final test before and after exercise skip for height using a meansuring tool that is Vertical jump Test. The method of processing data using descriptive statistics calculations and to test the hypothesis using the t test. The hypothesis proposed in this study is the effect of exercise skip for height to power leg muscle In the men’s volleyball team Panti Sosial Bina Remaja (PSBR) Rumbai Pekanbaru.The results of the ttest produced 3,46 and 1,796 ttable at the significant level of 0.05. Means ttest> t table. It can be concluded that H0 is greater than the Ha. So, the conclusion is there is a significant effect of exercise skip for height to power leg muscle In the men’s volleyball team Panti Sosial Bina Remaja (PSBR) Rumbai Pekanbaru. Key Words: Exercise skip for height. Power leg muscle